The Effect Of Career Development On Employee Performance In Smart Fast Global Education Pekanbaru - Winario, Mohd; Candra, Filtra; Khairi, Rifqil; Zakir, Muhammad (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
The purpose of this research is to find out the influence of career development on employee performance on Smart Fast Global Education Pekanbaru.. Its data analysis using descriptive and correlational methods with quantitative approaches, to determine the influence of independent variables (career development) on dependent variables (employee performance) is analyzed with simple linear regression using the SPSS program. The Effect of Career Development on Employee Performance at Smart Fast Global Education Institute Pekanbaru had a significant effect with a coefficient of determination of R2 of 0.358. This means that the employee performance variable (Y) is influenced by the career development variable (X) by 35.8%, , while the remaining 64.2% is explained by faktor-other factors that were not studied by the author. Variable career development (X) has a positive influence on employee performance (Y) with aregression coefficient of 0.414 indicating that if career development increases by 1 unit then employee performance variables will increase by 0.414,this means that thehigh career development will behigher. The results of the hypothesis test showed a calculated t value (4.60 1) > ttable (1,,685)) which means Ho was rejected and Ha accepted. It can be concluded that career development has a significant effect on employee performance